Act like it's your business : branding and marketing strategies for actors - Flom, Jonathan, 1977- (The Scarecrow Press, Incorporated, 2013)
In Act Like It's Your Business: Branding and Marketing Strategies for Actors, Jonathan Flom helps actors and others in the arts understand the power of branding. This guide walks the reader through the process of creating a personal brand for his or her small business and then marketing that brand and broadcasting it through every step of the process-from choosing clothing, arranging headshots, and designing resumes to selecting a repertoire, building a website ...